2021
DOI: 10.1093/ofid/ofab036
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Infection Among Health Care Workers Despite the Use of Surgical Masks and Physical Distancing—the Role of Airborne Transmission

Abstract: SARS-CoV-2 is transmitted mainly via respiratory droplets. A key question in COVID-19 pandemic is whether it could be transmitted via airborne route as well. We report for the first time SARS-CoV-2 nosocomial infections, despite using surgical masks and physical distancing. It may provide a possible evidence for airborne transmission of SARS-CoV-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
40
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 8 publications
0
40
0
2
Order By: Relevance
“…Given the transmission mechanism via respiratory droplets [28], head and neck surgery has been recognized as one of the specialties at the highest risk since the onset of the COVID-19 pandemic due to the invasive nature of examinations with patients not being able to wear a mask and the aerosol-generating procedures like ultrasonic scaling. In a multicentric survey (23 maxillofacial surgery departments) from Italy, 4% of maxillofacial residents tested positive for SARS-CoV-2 [29]. Reports like this caused an energetic discussion regarding the necessary measures to be taken in dental practices and clinics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the transmission mechanism via respiratory droplets [28], head and neck surgery has been recognized as one of the specialties at the highest risk since the onset of the COVID-19 pandemic due to the invasive nature of examinations with patients not being able to wear a mask and the aerosol-generating procedures like ultrasonic scaling. In a multicentric survey (23 maxillofacial surgery departments) from Italy, 4% of maxillofacial residents tested positive for SARS-CoV-2 [29]. Reports like this caused an energetic discussion regarding the necessary measures to be taken in dental practices and clinics.…”
Section: Discussionmentioning
confidence: 99%
“…However, emergency visits were increased 16-fold [33]. A multicentric survey performed 4 weeks after the pandemic started in Italy reported of an 87% decrease in outpatient visits and surgery, a reduction in general anesthesia surgery of 78% countrywide, whereas-although with a reduced incidence-the surgical management of trauma and oncology have been carried out [29]. An overall reduction of outpatient visits of 50% per week due to the measures implemented to contain the pandemic was seen in a university medical center in Germany [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the virus is transmitted only through larger particles (droplets) that fall to the ground within a metre or so after exhalation, then mask fit would be less of a concern. As it is, healthcare workers wearing surgical masks have become infected without being involved in aerosol generating procedures 111213. As airborne spread of SARS-CoV-2 is fully recognised, our understanding of activities that generate aerosols will require further definition.…”
mentioning
confidence: 99%
“…Faecal aerosols produced by toilet flushing were thought to be responsible, 11 reminiscent of the Amoy Gardens SARS outbreak in Hong Kong in 2003. There have also been several documented outbreaks in health care settings which were not only highly suggestive of airborne transmission but also demonstrated that physical distancing and the use of surgical masks is not always sufficient to prevent infection 12-15 . In contrast, a study of health care workers from Finland found that none of those using FFP2/3 respirators became infected 15…”
mentioning
confidence: 99%